Plant conservation: the seeds of success - Walker, T.; Harris, S.; Dixon, Kingsley (John Wiley and Sons, 2013)
In common with many other organisms, individual plant species are threatened with rapid, human-mediated range change and extinction, processes which over the long term are also important in species evolution. Conservation requires human action if it is to happen, let alone succeed. A major challenge to planning plant conservation is to answer the apparently simple question: how many plant species are found on earth? The enumeration of taxa is one-dimensional, and is only one aspect of conservation. Other important aspects are associated with pollinator and seed biology, whilst the judicial application of genetic analyses provides important insights for plant conservation protocols. Pollination services underpin the capacity of ecosystems for ongoing reproductive capacity, while ensuring genetic diversity is maintained. Seeds provide a complementary, cost-effective and efficient means for off-site (ex situ) conservation of plant species. The chapter finally presents orchid conservation as a case study in global issues in conservation.